2022
DOI: 10.21037/atm-22-2586
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the characteristics of symptomatic intracranial atherosclerotic plaques with stroke types and risk of stroke recurrence: a cohort study

Abstract: Background: Symptomatic intracranial atherosclerotic stenosis (sICAS) patients had a higher risk of stroke recurrence, and the risk of acute ischemic stroke (AIS) was higher than transient ischemic attack (TIA).Therefore, it is important to explore the risk factors associated with sICAS clinical subtypes and the risk of stroke recurrence. The purpose of this study was to investigate the association between intracranial arterial culprit plaque characteristics with sICAS clinical subtypes and the risk of stroke … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…The inclusion criteria for patient enrollment were as follows: (1) first onset of stroke within 4 weeks of HR-MR-VWI ( Ran et al, 2020 , Jiang et al, 2022 ); (2) acute IS within the unilateral MCA territory as observed on diffusion-weighted imaging (DWI); (3) presence of at least one cardiovascular disease risk factor: hypertension, diabetes mellitus, hyperlipidemia, hyperhomocysteinemia, smoking and/or drinking habits ( Song et al, 2020 , Jiang et al, 2022 ); (4) age of 18 years or older. The exclusion criteria were as follows: (1) presence of chronic IS or transient ischemic attack (TIA); (2) culprit vessel other than the ipsilateral MCA; (3) ipsilateral carotid artery stenosis ≥ 50% ( Song et al, 2020 , Xu et al, 2022 ); (4) patients with infarcts in multiple artery territories beyond MCA ( Li et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The inclusion criteria for patient enrollment were as follows: (1) first onset of stroke within 4 weeks of HR-MR-VWI ( Ran et al, 2020 , Jiang et al, 2022 ); (2) acute IS within the unilateral MCA territory as observed on diffusion-weighted imaging (DWI); (3) presence of at least one cardiovascular disease risk factor: hypertension, diabetes mellitus, hyperlipidemia, hyperhomocysteinemia, smoking and/or drinking habits ( Song et al, 2020 , Jiang et al, 2022 ); (4) age of 18 years or older. The exclusion criteria were as follows: (1) presence of chronic IS or transient ischemic attack (TIA); (2) culprit vessel other than the ipsilateral MCA; (3) ipsilateral carotid artery stenosis ≥ 50% ( Song et al, 2020 , Xu et al, 2022 ); (4) patients with infarcts in multiple artery territories beyond MCA ( Li et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The NIHSS score was used to assess the degree of neurological impairment and short-term outcome. Stroke recurrence was diagnosed when a new lesion exhibiting hyperintensity on DWI and hypointensity on apparent diffusion coefficient (ADC) images within the MCA territory was observed on follow-up MR examination, accompanied by corresponding neurological dysfunction ( Jiang et al, 2022 ). The patient with transit stroke symptoms without new infarction lesion on MRI was diagnosed as TIA instead of IS recurrence.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Wu XB et al used HR-VWI combined with hemodynamic indicators to analyze the relationship with ischemic stroke, and found that plaque enhancement and wall shear stress ratio were significantly associated with ischemic stroke [ 113 ]. This demonstrates the remarkable contributions of HR-VWI in improving patient outcomes and directing tailored interventions for ischemic stroke [ 94 , [114] , [115] , [116] ].…”
Section: Hr-vwi and Ischemic Strokementioning
confidence: 99%